Public Finance and Debt Crises in Southern Africa: A Push for Central Banks over Parliaments - Dunia Zongwe (Potchefstroom Electronic Law Journal)
In the soaring symphony of fiscal policy in Southern Africa, this paper orchestrates a new tune, proposing that central banks, not parliaments, should take the lead role in managing and taming sovereign debt. This proposal reacts to the adoption by the Southern African Development Community (SADC) of the Public Finance Management Model Law on July 14th last year – a law that empowers SADC parliaments, especially their public accounts committees (PACs), to oversee governments’ management of public debts. Among other things, this model law on public finance management (PFM) provides for debt ceilings and the steering of public debts towards SADC voluntary debt target of 50% of gross domestic product (GDP).